Evaluation of oxidative stress via protein expression of glutathione S-transferase and cytochrome p450 (CYP450) ısoenzymes in psoriasis vulgaris patients treated with methotrexate. (3rd April 2018) - Akbulak, Ozge; Karadag, Ayse Serap; Akdeniz, Necmettin; Ozkanli, Seyma; Ozlu, Emin; Zemheri, Ebru; Oguztuzun, Serpil
Abstract: Introduction: Oxidative stress is the imbalance between oxidant-antioxidant systems and may play a major role in the psoriasis pathogenesis. Cytochrome (CYP) is a family of enzymes that are responsible for the metabolism of various endogenous and exogenous substances such as drug metabolism. Most importantly, the antioxidant system is the glutathione S-transferases (GST), which decrease oxidative stress by reducing oxidative products. Aim: We aimed to evaluate the expressions of isoenzymes of GST and CYP families and the beneficial role of metotrexate (MTX) in this process. Material and methods: This study included 21 patients with psoriasis and 22 healthy subjects. We treated all the patients with 10–15 mg/week of MTX for minimum 12 weeks. Expressions of GST and CYP enzymes were assessed by immunohistochemical staining. Results: GSTK1, GSTM1 and GSTT1 expressions were significantly higher in the psoriasis tissues than in the control tissues ( p  < 0.05; p  < 0.05; p  < 0.05, respectively). In the psoriasis patients, GSTO1 expression was similar the control group. CYP1B1 and CYP2E1 expressions were significantly higher in the pre-treatment and post-treatment psoriasis tissues than in the control tissues ( p  < 0.05; p  < 0.05; p  < 0.05; p  < 0.05, respectively). Conclusion: We found a significant increase in the tissue levels of, either expression of GST, or CYP, which has important role in drug metabolism and oxidative stress. MTX treatment resulted in marked clinical improvement, yet we found that MTX did not have any significant effect on these parameters. CYP2E1 is especially the most important enzyme for MTX metabolism since it is the primarily responsible of the toxic metabolism of various drugs. The other experimental studies involving greater number of patients and other different drug are needed to enlighten the role of oxidant and antioxidant systems and the other possible mechanisms for the pathogenesis of psoriasis.